2013
DOI: 10.3390/s130912140
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Fabricating an Inverted Mesa-Type Quartz Crystal Resonator Using a Cheap Wet Etching Process

Abstract: In this study, a miniaturized high fundamental frequency quartz crystal microbalance (QCM) is fabricated for sensor applications using a wet etching technique. The vibration area is reduced in the fabrication of the high frequency QCM with an inverted mesa structure. To reduce the complexity of the side wall profile that results from anisotropic quartz etching, a rectangular vibration area is used instead of the conventional circular structure. QCMs with high Q values exceeding 25,000 at 47 MHz, 27,000 at 60 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…In this study, the etching area is designed to be 2500 μm in diameter, the measured results indicates that the electrode dimension larger than 2100 μm will cause a sharp drop of Q value (1386) due to the small distance between the electrode and the edge of vibration area as we discussed before [20]. Accordingly, the frequency stability becomes worse, and the standard deviation was measured to be large as 53 Hz, which is considered too large for actual application.…”
Section: Resultsmentioning
confidence: 91%
“…In this study, the etching area is designed to be 2500 μm in diameter, the measured results indicates that the electrode dimension larger than 2100 μm will cause a sharp drop of Q value (1386) due to the small distance between the electrode and the edge of vibration area as we discussed before [20]. Accordingly, the frequency stability becomes worse, and the standard deviation was measured to be large as 53 Hz, which is considered too large for actual application.…”
Section: Resultsmentioning
confidence: 91%
“…Ever since 1964, King Jr. postulated that the sensitivity of detection was inversely proportional to the square of the electrode diameter and the resonator thickness. Recently, Liang et al (2013) reported that for HFF-QCM chips of about 73 MHz, quality factor increases as electrode diameter decreases for a given range. Thus, there is a need to find out a crystal design compromise in order to get the optimal electrode diameter to crystal thickness ratio for a given HF frequency.…”
Section: Carbaryl Standard Curves: Electrode Diameter Selection and Amentioning
confidence: 99%
“…The detailed fabrication process and chip characterization have been reported in previous studies from our laboratory. (20,21) The dimensions of the QCM chip were 5 (length) × 5 (width) × 0.1 (thickness) mm 3 . The fundamental frequency was higher than 38 MHz, and the quality factor was larger than 20000 in air and 1000 in pure water.…”
Section: Methodsmentioning
confidence: 99%
“…A flow injection system was established to introduce the PB solutions as reported in our previous report. (20) The flow-injection-based measurement system consisted of a syringe pump, an injector, a tailor-made flow cell, and an impedance analyzer (Agilent 4294A). Distilled pure water was loaded into the syringe pump, and variable PB solutions were introduced through the injector.…”
Section: Measurement Methodsmentioning
confidence: 99%